2018
DOI: 10.2485/jhtb.27.1
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Bone Regeneration using iPS Cell-Derived Neural Crest Like Cells

Abstract: Induced pluripotent stem (iPS) cells represent a powerful source for cell-based tissue regeneration because they are patient-specific cells and can differentiate into specialized cell types. Previously, we have demonstrated the derivation of neural crest like cells from iPS cells (iPS-NCLCs), and these cells have the potential to diff erentiate into dental mesenchymal cells, which subsequently diff erentiate into odontoblasts and dental pulp cells. In this study, we show that iPS-NCLCs can diff erentiate into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In comparison to human BM‐MSCs, tissue engineered constructs of MSCs from iPSC‐derived NCLSCs did not undergo chondrogenesis in vivo nor did they effectively repair osteochondral defects 158 . On the other hand, mouse iPSC‐NCLSC‐MSCs transplanted into calvarial defects differentiated into osteoblasts, produced no tumors, and contributed to bone regeneration 159 . These studies highlight how these derived cells may behave differently in vivo.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In comparison to human BM‐MSCs, tissue engineered constructs of MSCs from iPSC‐derived NCLSCs did not undergo chondrogenesis in vivo nor did they effectively repair osteochondral defects 158 . On the other hand, mouse iPSC‐NCLSC‐MSCs transplanted into calvarial defects differentiated into osteoblasts, produced no tumors, and contributed to bone regeneration 159 . These studies highlight how these derived cells may behave differently in vivo.…”
Section: Introductionmentioning
confidence: 91%
“…PSC‐derived NCLSCs have also been differentiated into various cell types, including MSCs, osteocytes, and chondrocytes, that are beneficial for bone, cartilage, and tendon regeneration 30,156‐160 . Xu et al examined whether iPSC‐derived NCLSCs could repair a rat patellar tendon window defect.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-BMP2 antibody/BMP2 immune complex induces iMSCs to acquire osteogenic phenotype and mineralization, which suggests that antibody-induced osteogenic differentiation could be an alternative technology for iPSC-based tissue regeneration [115] . Kikuchi et al recently differentiated iNCCs into iMSCs, which were differentiated into osteoblasts, adipocytes, and chondrocytes in vitro, and had capability to regenerate craniofacial bone in vivo without tumor formation [116] .…”
Section: Ipscs In Dentistrymentioning
confidence: 99%
“…Yanaga et al (2006) made an attempt to use a composite of autologous human auricular chondrocytes with autologous serum for craniofacial augmentation in a pilot clinical study. Otsu's group revealed that neural crest-like cells from iPS cells could differentiate into osteoblasts and contribute to craniofacial bone regeneration without tumor formation in vivo (Kikuchi et al, 2018). This method could resolve the limitation of insufficient source of reconstructive material.…”
Section: Bonementioning
confidence: 99%